Operations and Supply Chain Management, 2nd Edition - David A. Collier; James R. Evans (Cengage Learning, 2020)
Clearly introduce today's fundamental concepts and applications of operations and supply chain management using the reader-friendly approach in Collier/Evans' OPERATIONS AND SUPPLY CHAIN MANAGEMENT, 2E. The authors integrate numerous solved problems to illustrate key formulas and computations as students learn to complete both manual and digital calculations using Excel spreadsheet templates and other Excel models for optimization and simulation. New, expanded and proven Review and Discussion Questions, Experiential Activities, Cases, Computational Problems and Exercises and Excel-Based Problems guide students in applying qualitative and quantitative reasoning with the latest operations management (OM) and supply chain management (SCM) concepts and tools. In addition, new content examines process analysis and resource utilization, analytics in OM, capacity measurement, applications of linear optimization and other leading topics.